Perempuan Usia 24 tahun dengan GERD : Laporan Kasus - Muhammad Ihsan Fariqy; Tutik Ernawati (CV. Jasa Sukses Abadi, 2026)
Gastroesophageal Reflux Disease (GERD) is a disorder caused by the reflux of gastric contents into the esophagus and is influenced by biological, behavioral, psychological, and social factors, requiring a comprehensive family medicine approach. We report the case of a 24-year-old woman who presented to Kalirejo Primary Health Center with worsening epigastric pain for two days, accompanied by abdominal fullness, heartburn, nausea, and vomiting. She had experienced similar symptoms for the previous two years, with risk factors including irregular eating habits, frequent consumption of spicy foods, skipping breakfast, overweight, and psychological stress related to family financial problems. The diagnosis was established based on history taking, physical examination, and a GERD-Q score of 11. Management consisted of pharmacological therapy with omeprazole, antacids, and domperidone, combined with non-pharmacological interventions using a patient-centered, family-focused, and community-oriented approach through health education, dietary modification, stress management, and active family involvement. Follow-up after three home visits demonstrated clinical improvement, increased patient and family knowledge (pre-test score 50 to post-test score 80), better treatment adherence, and positive behavioral changes, including regular meal patterns, reduced consumption of trigger foods, and stronger family support. A comprehensive family medicine approach plays an important role in controlling risk factors, improving quality of life, and preventing GERD recurrence.